Pencantuman Label Alergen dalam Pelabelan Produk Pangan Sebagai Bentuk Perlindungan Konsumen - Danang Wahyu Muhammad; Izzy Al Kautsar; Emmy Latifah (Jurnal Hukum IUS QUIA IUSTUM, 2023)
The purpose of this study is to present a normative analysis of the labeling of food products in Indonesia and the relationship between information disclosure on food labels and the implementation of consumer protection. This research uses normative juridical methods. The results conclude that first, the current global food issue is the danger of consuming food ingredients that contain allergens. The United States, Singapore and Japan have required the inclusion of allergen information in the labeling of food products in their respective National Laws. This is a lesson for Indonesia to require the inclusion of allergen information in the National Law. Therefore, a limited revision of Article 97 paragraph 3 of the Food Law is needed to include the obligation to include warnings for allergen content on food labels. Second, many food products do not display information in accordance with reality and its original content, which is detrimental to consumers. Consumer protection in food regulation through food labeling departs from the State's efforts to safeguard the rights and interests of these consumers so that they are not harmed by profit-oriented producers by way of processing and distributing fair and healthy food products based on the principle of information disclosure.Keywords: Disclosure of Information; Food Labels; Consumer Protection AbstrakTujuan penelitian ini adalah analisis normatif terhadap labelisasi produk pangan di Indonesia dan hubungan antara keterbukaan informasi pada label pangan terhadap implementasi perlindungan konsumen. Penelitian ini menggunakan metode penelitian yuridis normatif. Hasil dari penelitian ini menyimpulkan, pertama, isu pangan global saat ini adalah bahaya konsumsi bahan pangan yang mengandung alergen. Amerika Serikat, Singapura, dan Jepang telah mewajibkan pencatuman keterangan alergen dalam pelabelan produk pangan dalam Undang-Undang Nasional masing-masing, ini menjadi pelajaran bagi Indonesia untuk mewajibkan pencatuman keterangan alergen dalam Undang-Undang Nasional. Maka diperlukan revisi terbatas atas Pasal 97 ayat (3) UU Pangan untuk memasukan kewajiban pencantuman peringatan kandungan alergen dalam label pangan. Kedua, banyak produk pangan yang tidak menampilkan informasi sesuai dengan kenyataan dan kandungan aslinya sehingga merugikan konsumen. Perlindungan konsumen dalam pengaturan pangan melalui label pangan berangkat dari upaya negara untuk menjaga hak-hak dan kepentingan konsumen tersebut agar tidak dirugikan oleh produsen yang berorientasi profit dengan cara pengusahaan dan pengedaran produk pangan yang adil dan sehat berdasarkan asas keterbukaan informasi.Kata-kata Kunci: Keterbukaan Informasi; Label Pangan; Perlindungan Konsumen